Electronic combination lock with high security features - HARVEY MICHAEL P; MILLER J. C (2005)
A self-powered electronic combination lock including a lock mechanism having locked and unlocked conditions. A rotatable dial is used to input a numerical combination code for changing the lock mechanism from the locked condition to the unlocked condition. An electronic display operates to display individual numbers of the combination code as the dial is rotated and a control is electrically connected with the dial and the electronic display. The control changes the numbers shown in the display as the dial is rotated in a single direction and the control is operable to sense a change in the direction of dial rotation. An electricity generating device is connected with the dial and the control and operates through dial rotation to generate electricity to power the control.